Peran Rubi Community dalam Penerapan Strategi Public Relations Untuk Membangun Citra Merek Avoskin Beauty - Ilma Nafi’atul Jannah; Hadiati; Novita Damayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the role of the RUBI Community in implementing public relations strategies to build the brand image of Avoskin Beauty. Using a qualitative case study approach within a constructivist paradigm, the research applies New Media theory, the R.A.C.E process, and the 7C’s model. Data were collected through triangulation of in-depth interviews, participant observation, and documentation, and analyzed using the Miles & Huberman model. The findings reveal that the RUBI Community functions both as a communication channel and as a CSR initiative focusing on women’s empowerment. This dual role significantly enhances Avoskin’s image as an innovative and affordable brand, while strengthening consumer loyalty. The study concludes that community-based PR strategies can effectively foster emotional engagement and brand advocacy, offering practical implications for beauty brands seeking to integrate social values into their communication strategies.